Risk Factors of Maternal Nutrition Status During Pregnancy to Stunting in Toddlers Aged 12–59 Months - Hemi Fitriani; Achmad Setya R; Popy Nurdiana (Jurnal Keperawatan Padjadjaran, 2020)
Maternal nutrition status during pregnancy highly contributed to risk factors of stunting among children. Bone ossification approximately begins in the sixth weeks of embryonic development and continues to the end of pregnancy. However, inadequate nutrient supply in pregnant women harmed fetal growth. The study aimed to identify the association between pregnant women’s nutrition status and stunting. The case-control study using the retrospective design involved mothers with children aged 12–59 months. A proportional random sampling technique was applied to select participants. The sample was 80 toddlers, divided into 40 stunted, and 40 non-stunted toddlers. Data were taken from 27 April to 3 May 2019 through observations following the Mother and Child Health handbook and children’s height. Weight gain calculation during pregnancy determined the maternal nutrition status, referred to as maternal pre-pregnancy body mass index. The univariate analysis used frequency distribution, while bivariate analysis used the chi-square test. This study obtained approval from The Health Research Ethics Committee of the Institute of Health Science of General Achmad Yani, Cimahi. The mothers’ poor nutritional status caused as many as 85% of stunted toddlers’ prevalence during pregnancy. Results showed that maternal nutritional status during pregnancy was significantly associated with stunting among children (p-value: 0.000). The OR value was 13,222, which means children born to mothers with inadequate nutrient supply during pregnancy were more likely to be stunted as much as 13,222 times, than children born to mothers who had good nutrient supply. It is recommended that health workers prevent stunting from pregnancy by providing supplementary food to pregnant women, and promoting the health of the maternal nutritional status during pregnancy. Suggestions for pregnant women is to increase nutrient intake and nutritional status during pregnancy to prevent stunting in children.